Pemanfaatan Kompos Tandan Kosong Kelapa Sawit untuk Meningkatkan Pertumbuhan Tanaman Kayu Putih (Melaleuca cajuputi) di Lahan Pasca Tambang Batubara - Agus Ari Subagio; Irdika Mansur; Rita Kartika Sari (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2018)
Compost of oil palm empty bunches can improve fertility and soil nutrient on ex-mining land. This study aimed to evaluate the effect of oil palm empty fruit bunches composted on growth of Melaleuca cajuputi on post-mining land. This research was conducted at field for 3 months. The application was done at 1 to 3 years plant age. A single factor of empty fruit bunch compost organized on RCBD with 4 treatments and 4 replication. The results showed the compost able to increase growth of M. cajuputi. The best application was K1 (5 kg plant-1) increased height of 1 and 2 years plant age respectively by 67.82 and 38.86%. K2 (7.5 kg plant-1) at 3 years old increased by 30.16%. While the highest yield of diameter increased was on K2 (7.5 kg plant-1) at 1 and 3 years plant age (46.05% and 30.85%). The 2 year plant age with dose K3 (10 kg plant-1) was increased of 32.09%. In general, the application of EFB compost such as K1 treatment (5 kg plants-1) was reached the best dose of 1 and 2 year plant age and K2 treatment (7.5 kg plant-1) gave the best response for 3 years of plant age.Keywords: empty fruit bunch, EFB, Melaleuca cajuputi, postcoal-mining land